Sistem Monitoring Denyut Jantung Menggunakan NodeMCU dan MQTT - Falachudin Akbar; Rizal Maulana; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Heart rate is one of the basics to know basic health. Symptoms from the heart rate is tachycardia and bradycardia, that conditions are not nomal. The incidence of abnormal symptoms in the heart rate may indicate a disease. Therefore, this research is designing tools for heart rate monitoring. This heart rate monitoring system measures the heart rate by reading the pulse sensor value, after that nodemcu will process reading heart rate value to get BPM (Beat per Minute). After getting the value of BPM, System check if more than 100 will send SMS danger tachycardia, if less than 60 will send SMS danger bradikardia. System will send BPM data to the thingspeak channel using MQTT. The system will always be ready to receive SMS request heart rate which will reply SMS with BPM value. The results of the system functionality test can be successfully performed and the results of the heart rate reading test resulted in a percentage error of 2.6%. In testing heart rate data transmission to the Thingspeak channel, sending SMS warnings, and replying to sms with the latest heart rate can be successfully done.